STATUS JANDA AKIBAT PERCERAIAN DAN IMPLIKASINYA TERHADAP KELUARGA : Studi Teori Fungsionalisme Struktural di Desa Gedangsewu Kecamatan Pare Kabupaten Kediri - M. Abdul Hakim (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Being widowed due to divorce is an emotional challenge, which makes women who are widowed will face severe challenges, especially in terms of relationships or relationships with their family environment, especially children and parents due to their new status, if the widow is really ready and able to face the new reality as a widow and single parent, maybe they can survive carrying out their function as a single parent, but if on the contrary, this will have a negative impact and is prone to post-divorce conflict on family harmony, especially towards children and parents. Plus economic problems and the social burden of accepting the reality of being a widow. This research is qualitative research. Based on its type, it includes field research. The data collection method used is observation and interview. Then analyzed using Robert K. Merton's Structural Functionalism theory. This research produced two important findings. First, as a result of the divorce, a wife or widow has a new role or dual role in the family, namely domestic and public roles, widows assess themselves that their family is harmonious. The harmony in building their family is seen from the way they build relationships with family members, in terms of leadership and decision-making in the family. then the division of roles in the household and solving problems in the household. Second, widowed women consider themselves to have carried out the functions of the family structure well. From the process of roles or functions carried out by the widows, four typologies of roles or functions of widows were found as they played or functioned as economic functions, family functions, social functions, and religious functions, from each function or typology, they have manifest functions, namely expected functions (intentional) and latent functions (unintentional).